2015
DOI: 10.1177/0004563214568685
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin in the assessment of bacteraemia in emergency department patients: results of a large retrospective study

Abstract: When procalcitonin is used as a serum marker for ruling out bacteraemia, a cut-off of 0.1 ng/mL may be used. Procalcitonin improves the diagnostic accuracy of existing markers of bacteraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
6
1
4
Order By: Relevance
“…We found remarkably high AUROCs of CRP level and PCT level compared to previous studies [6, 14, 18, 19, 26]. These studies, however, excluded patients without SIRS or suspected infection, or they compared patients with bacteremia to patients without bacteremia.…”
Section: Discussioncontrasting
confidence: 42%
“…We found remarkably high AUROCs of CRP level and PCT level compared to previous studies [6, 14, 18, 19, 26]. These studies, however, excluded patients without SIRS or suspected infection, or they compared patients with bacteremia to patients without bacteremia.…”
Section: Discussioncontrasting
confidence: 42%
“…The impetus for promptly initiating appropriate broad-spectrum antimicrobial therapy must be weighed against the concern for reducing unnecessary antimicrobial therapy and potential harms, such as drug resistance, Clostridium difficile infections, and adverse drug effects (3). The lack of a specific test to assist clinicians in early decision-making regarding initiation and discontinuation of antimicrobial therapy for severe infection and presumed sepsis has led to expanded interest in inflammatory biomarkers, such as procalcitonin (PCT) (4-12).Previous trials evaluating PCT have used value ranges to guide clinical decisions within the construct of initiating and discontinuing antimicrobial therapy using clinical criteria (4,5,(7)(8)(9)(10)(12)(13)(14). By using serial measurements and established cutoff values in intensive care units (ICUs), these studies have shown that PCT values guide antimicrobial therapy (13-18).…”
mentioning
confidence: 99%
“…Previous trials evaluating PCT have used value ranges to guide clinical decisions within the construct of initiating and discontinuing antimicrobial therapy using clinical criteria (4,5,(7)(8)(9)(10)(12)(13)(14). By using serial measurements and established cutoff values in intensive care units (ICUs), these studies have shown that PCT values guide antimicrobial therapy (13-18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Bacterial infections that reach blood are called bacterteremia. [3] Cases of bacteremia can be established through culture testing and drug sensitivity which is the gold standard examination. [4] Bacteremia can cause death with a mortality of 30% where high mortality is associated with the establishment of inaccurate and late diagnoses.…”
Section: Introductionmentioning
confidence: 99%